2005
DOI: 10.1007/s00348-005-0996-2
|View full text |Cite
|
Sign up to set email alerts
|

Flow characteristics of spray impingement in PFI injection systems

Abstract: Internal Combustion engines with multi-point, or sequential, fuel injection have a fuel injector for each cylinder, usually located so that they spray right at the intake valve. While in a fully warmed-up engine, fuel droplets vaporize before entering the combustion chamber, at cold start, a significant proportion of the injected gasoline deposits on the intake port and valve surfaces. The result is a deterioration of mixture homogeneity, decreased metering accuracy and increased hydrocarbon emissions. A bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(31 citation statements)
references
References 18 publications
(19 reference statements)
0
30
0
Order By: Relevance
“…Although this has been relatively successful for continuous water sprays, Panão and Moreira [30], confirmed that it cannot accurately describe intermittent fuel sprays. Furthermore, a form of predicting the size and velocity distributions of secondary droplets was also developed but unfortunately it does not include any elements resulting from the previous analysis on interaction phenomena.…”
Section: Table 11mentioning
confidence: 86%
See 2 more Smart Citations
“…Although this has been relatively successful for continuous water sprays, Panão and Moreira [30], confirmed that it cannot accurately describe intermittent fuel sprays. Furthermore, a form of predicting the size and velocity distributions of secondary droplets was also developed but unfortunately it does not include any elements resulting from the previous analysis on interaction phenomena.…”
Section: Table 11mentioning
confidence: 86%
“…Therefore, most quantitative and qualitative results are obtained assuming that interaction effects are implicit. This approach was followed in Panão and Moreira [30], and it was possible to show a 'cross-talk' effect between the impacting spray momentum and the film radial spreading, further imparting momentum to secondary droplets in outward regions. This interaction result could only be observed when the analysis considered the spray as a whole.…”
Section: Table 11mentioning
confidence: 97%
See 1 more Smart Citation
“…In dense sprays, however, the behaviour of single drop impacts is altered by multiple drop interactions, such as those occurring between droplets in the vicinity of each other [3][4][5] and between consecutive drop impacts [6]. Moreover, when the mass rate of liquid adhered to the surface overcomes the vaporization rate, a liquid film forms which spreads over the surface; crown development and thus secondary atomization is mainly influenced by local variations of the liquid film induced by drop impact; re-atomized droplets may emerge from liquid jets induced by pressure fluctuations generated by multiple drop impacts in the liquid film; interfacial activity in the vicinity of the wall caused by successive injections induce vertical oscillations, which may trigger a chain of ejection-and-re-impaction of droplets with a rate faster than the injection frequency [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Drop impact phenomena on a surface widely occurs in practical engineering fields, which include spray cooling [1], spray coating [2], jet printing [3] and fuel injection in an internal combustion engine [4], among others. Drop behavior differs upon impact on a dry or wet surface.…”
Section: Introductionmentioning
confidence: 99%